PRESCRIPTION PATTERN OF ANTI-HYPERTENSIVE MEDICATIONS IN PATIENTS WITH HYPERTENSION AT A TERTIARY CARE HOSPITAL, ASSAM - ARITRA GUPTA; BARMAN, SARAJITA; ROY, DOLLY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The aim of our study is to analyze the pattern of prescription of medications used for managing hypertension (HTN) at a tertiary care hospital and assess the comorbidities associated with HTN. Methods: This prospective study has been conducted for duration of 6 months in the Department of Medicine of Silchar Medical College and Hospital. Prescriptions of both genders diagnosed with primary essential HTN and patients receiving or advised to start antihypertensive medications were included in the study. Results: One hundred and fifty prescriptions have been evaluated in the study duration, 42% are female and 58% male. Monotherapy (69%) followed by dual therapy (26%) and multidrug therapy (5%) have been prescribed to the patients. Calcium channel blockers (CCBs) (48%) are the most widely used drugs, along with angiotensin receptor blockers (ARBs) (29%), beta-blockers (BBs) (11%), diuretics (6%), and angiotensin-converting enzyme inhibitors (6%) in single drug therapy. ARB+CCB followed by ARB+diuretic and ARB+BB were used in dual therapy. In triple therapy, the most preferred therapy was ARB+CCB+diuretic, and then ARB+CCB+BB. Dyslipidemia (38%), followed by Type 2 diabetes mellitus (DM) (34%), and chronic kidney disease (CKD) (19%) were the most common associated comorbidities. Conclusion: Monotherapy was frequently prescribed regimen followed by dual therapy and multidrug therapy. In single-drug therapy, CCB was mostly used, and then ARB. In dual therapy CCB+ARB was the most preferred treatment. Dyslipidemia was most frequently associated with HTN, followed by DM and CKD. Prescription patterns of anti-hypertensive moderately followed the World Health Organization recommendations for HTN.